Thermal assessment of a new planar thermal diode integrated collector storage solar water heater in different partial vacuums: An experimental study. (May 2023) - Farzan, Hadi; Ameri, Mehran; Mahmoudi, Mojtaba
Abstract: Thermal diodes are novel mechanisms with high thermal resistance in one direction and low thermal resistance in the other. The current study introduces a new planar thermal diode integrated collector storage (ICSs) system and analyzes its transient dynamics and performance under field conditions in several scenarios, including operating at atmospheric pressure and partial vacuums: P total = 0.7 atm and 0.5 atm. The acquired data illustrate that the collector has approximately the same transient dynamics during the collection period, while differences pronounce during the retention period. Utilizing partial vacuums is tricky and may cause to decrease in performance; however, the best retention and collection efficiencies were obtained at 16.97% and 29.33% when P total = 0.7 atm was utilized. Increasing the partial vacuums to P total = 0.5 atm decreases the retention efficiency significantly to nearly 3.26%. The heat gain (forward mode) coefficient was not affected significantly by partial vacuums. However, the heat loss (reverse mode) coefficient was reduced by nearly 17.63% at P total = 0.7 atm compared to atmospheric pressure. The calculated heat gain and heat loss coefficients are 9.28 W/k and 19.65 W/k at P total = 0.7 atm; hence, the constructed thermal diode successfully serves as a unidirectional heat transfer mechanism.